Analisis Jenis-Jenis Tokoh dalam Novel “Mengungkit Pembunuhan” Karya Agatha Chiristie - Leki, Irma (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the different types of characters in Agatha Christie's Mengungkit Murder. By adopting a qualitative approach and descriptive analysis method, this study identifies the characters in the novel and their roles and relationships in the storyline. The research data were obtained through literature study and text analysis, which were then analyzed using content analysis techniques. The results show that the characters in the novel not only serve as plot drivers, but also reflect broader themes, such as justice and betrayal. This research is expected to make a significant contribution to literary studies, especially in understanding characterization in Agatha Christie's works.